Manifold Molecular Signaling Targets of Tropolones in Multifarious Diseases - Fathima, Dr. Mohamed Zerein (Asian Journal of Pharmaceutics (AJP), 2021)
Tropolones are strewed phytochemicals having scaffold contains seven-membered ring system belongs to a family of Cupressaceae plants. Tropolone derivatives targeting multiple signaling transcription factors, cell cycle regulatory components, proteins, growth factors, kinases, and cytokines also involved in inflammatory mechanisms as well as involved in antioxidant, antimicrobial, anti-inflammatory, antithrombotic, and anticancer activities. To identify the therapeutically potent pharmacophores from the natural components is the long-term focus in pharmaceutical industry. Our preliminary findings on Hinokitiol (HIOL) showed binding potential in mitogen-activated protein kinase and ABL proto-oncogene 1 by in silico docking method perhaps in apoptosis of several cancers. This review aimed at gathering most of the available information to document the potential efficacy of tropolones and its molecular mechanisms. Although natural products usually have fewer activities compared with synthesized compounds, it will shed a light on studies aiming to discover new drugs from tropolone derivatives for targeting multiple signaling mechanisms for various diseases.